The Origin of the Jews : the Quest for Roots in a Rootless Age - Weitzman, Steven, 1965- (Princeton University Press, 2019)
The scholarly quest to answer the question of Jewish origins The Jews have one of the longest continuously recorded histories of any people in the world, but what do we actually know about their origins? While many think the answer to this question can be found in the Bible, others look to archaeology or genetics. Some skeptics have even sought to debunk the very idea that the Jews have a common origin. Steven Weitzman takes a learned and lively look at what we know-or think we know-about where the Jews came from, when they arose, and how they came to be. He sheds new light on the assumptions and biases of those seeking answers-and the religious and political agendas that have made finding answers so elusive. Introducing many approaches and theories, The Origin of the Jews brings needed clarity and historical context to this enduring and divisive topic.